INTEGRATING SHORT STORIES IN ENGLISH CLASSES FOR INDONESIAN STUDENTS: A CRITICAL REVIEW - Muhammad Alvin Firmansyah; Toyyibah Toyyibah (Universitas Wiralodra, 2025)
The integration of short stories in English language teaching has emerged as a compelling approach, offering multifaceted benefits for Indonesian students. While previous studies have explored the use of short stories in EFL contexts, this review synthesizes findings to offer actionable strategies tailored to Indonesian classrooms. Drawing on a systematic review of 15 studies from 2020 to 2024 using PRISMA methodology, this research examines the benefits, challenges, and strategies associated with using short stories in English language teaching. The findings highlight that short stories effectively enhance reading comprehension, vocabulary acquisition, and critical thinking through strategies such as think-pair-share, collaborative learning, and the 3-2-1 reading comprehension method. These approaches foster active engagement and align well with Indonesia's collectivist culture and educational needs. However, key challenges persist, including students' low interest in reading, limited teaching resources, and inadequate teacher training. In order to address these issues, this review emphasizes the importance of increasing support for teacher development and resource accessibility. By offering practical insights and culturally relevant strategies, this study contributes to the growing discourse on literature-based teaching and its potential to transform EFL education in Indonesia.